2021
DOI: 10.3389/fmicb.2021.657562
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome Study of Escherichia coli Devoid of Ser/Thr Kinase YeaG During the Metabolic Shift From Glucose to Malate

Abstract: Understanding phosphorylation-mediated regulation of metabolic enzymes, pathways, and cell phenotypes under metabolic shifts represents a major challenge. The kinases associated with most phosphorylation sites and the link between phosphorylation and enzyme activity remain unknown. In this study, we performed stable isotope labeling by amino acids in cell culture (SILAC)-based proteome and phosphoproteome analysis of Escherichia coli ΔyeaG, a strain lacking a poorly characterized serine/threonine kinase YeaG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…3d). The site occupancy of S177 and T179 was recently reported to be around 15% during growth on glucose 13 , a percentage that significantly decreases TpiA in vitro activity (Supplementary Fig. 1) and hence glycolytic flux.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…3d). The site occupancy of S177 and T179 was recently reported to be around 15% during growth on glucose 13 , a percentage that significantly decreases TpiA in vitro activity (Supplementary Fig. 1) and hence glycolytic flux.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, phosphoregulation may also be prevalent in bacteria, although only a few S/T-and Y-kinases and phosphatases are known and their in vivo substrates and regulators remain poorly characterized 12,13 . Mere detection of a phosphosite provides little evidence for function 14,15 , which is typically inferred indirectly from phosphosite conservation, co-occurrence with other modifications, and correlation of the degree of protein phosphorylation with physiological variables such as metabolic flux [16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Similar to eukaryotes, the genome of E. coli contains kinases and acetyltransferases that enzymatically catalyze protein phosphorylation and acetylation, respectively, but the knowledge about their targets is limited. 10,14,15 Additionally, proteins can be non-enzymatically modified by reactive metabolites, and some of these chemical modifications can be reversed, providing an additional layer of regulation to cellular processes. 16 The highenergy metabolite acetyl phosphate (AcP) can non-enzymatically acetylate proteins, 17 and its intracellular abundance has been linked to the acetylation of at least a third of all detected acetylation sites in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we showed that, despite distant homology with (cAMP)-dependent protein kinases for its C-terminal domain (12) and with the Ser/Thr kinase YeaG from E. coli (13)(14)(15), no autophosphorylation or kinase activity was detected for PrkA whatever the conditions tested. In addition, our data did not highlight an ATP binding site in the C terminal domain of PrkA.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, no PrkA autophosphorylation was detected which was surprising since STPKs generally need to be autophosphorylated to be active. Recently, a homologous protein from Escherichia coli, YeaG, has been shown to be indeed a kinase that autophosphorylates (14) and phosphorylates AceA, the isocitrate lyase involved in the glyoxylic cycle, in the presence of malate (15), but this catalytic pathway is missing in B. subtilis.…”
Section: Introductionmentioning
confidence: 99%